2010
DOI: 10.1155/2010/437809
|View full text |Cite
|
Sign up to set email alerts
|

Atherogenic Factors and Their Epigenetic Relationships

Abstract: Hypercholesterolemia, homocysteine, oxidative stress, and hyperglycemia have been recognized as the major risk factors for atherogenesis. Their impact on the physiology and biochemistry of vascular cells has been widely demonstrated for the last century. However, the recent discovery of the role of epigenetics in human disease has opened up a new field in the study of atherogenic factors. Thus, epigenetic tags in endothelial, smooth muscle, and immune cells seem to be differentially affected by similar atherog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 57 publications
(62 reference statements)
1
17
0
Order By: Relevance
“…DNMT3L lacks the cytosine methylation activity and functions as a regulatory factor in germ cells (17). The functional roles of DNMT2 are slowly emerging, and recent studies suggested its involvement in tRNA methylation (17). Our findings show that the attenuation of either DNMT1 or DNMT3B alone did not affect NPC1L1 mRNA expression.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…DNMT3L lacks the cytosine methylation activity and functions as a regulatory factor in germ cells (17). The functional roles of DNMT2 are slowly emerging, and recent studies suggested its involvement in tRNA methylation (17). Our findings show that the attenuation of either DNMT1 or DNMT3B alone did not affect NPC1L1 mRNA expression.…”
Section: Discussionmentioning
confidence: 52%
“…DNA methylation is mediated by DNMTs that catalyze the transfer of methyl groups from S-adenosylmethionine to the cytosine residue in the CpG dinucleotides (17). Three distinct families of DNMTs, DNMT1, DNMT2, and DNMT3, have been identified in mammals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an in-vivo model using 20-week old female apo E +/-mouse offspring from apo E -/-and wild-type mothers, it was shown that both prenatal induced and diet-induced hypercholesterolemia influenced histone methylation and lysine methyltransferase expression in vasculature. Moreover, these epigenetic modifications were different in endothelial cells and smooth muscle cells, suggesting the existence of a cell -specific responsiveness to a similar stimulating factor (11,12).…”
Section: Influence Of Epigenetics Changes On Lipid Metabolism In Metamentioning
confidence: 97%